Navigating the AI landscape in SMEs: Overcoming internal challenges and external obstacles for effective integration - Roziah Mohd Rasdi; Nordahlia Umar Baki (PLoS ONE, 2025)
Artificial intelligence (AI) integration in small and medium-sized enterprises (SMEs) is hampered by a variety of internal and external challenges. This article analyses these hurdles and underlines the need of an adaptation framework designed particularly for SMEs. The study collects primary data by conducting detailed interviews with representatives from six different SMEs in distinct sectors. The results indicate substantial internal obstacles, including reluctance to change, fear of job displacement by technology, and restricted resources, all of which impede the incorporation of AI. SMEs encounter a dynamic technological landscape, stringent regulatory requirements, and intense rivalry externally, necessitating agile and prompt strategy adjustments, a challenge often faced by SMEs. Ultimately, this research highlights the need of creating AI implementation plans that are customized to the distinct requirements and situations of SMEs. More adaptable and supportive legislative frameworks are essential to assist these enterprises in efficiently using AI and staying competitive in the digital era. This study contributes to the current discourse on technological progress in SMEs and establishes the foundation for next policies and initiatives designed to enhance their competitive edge using AI technology.